Preventive generation maintenance scheduling- A simulated annealing approach to use in competitive markets - João Tomé Saraiva (2010)
The scheduling of preventive maintenance actions of generators is not a new problem but gained in recent years a new interest with the advent of electricity markets. In this paper we report the research on this topic developed during the preparation of the MSc Thesis of the second author. In this paper we formulate the problem as a mixed integer optimization problem and we describe the use of Simulated Annealing to solve it. Simulated Annealing is a very appealing metaheuristic easily implemented and providing good results in numerous optimization problems. The paper includes results obtained for a Case Study based on a realistic generation system. This research work was proposed and developed with the collaboration of the third and fourth authors, from EDP Produção, Portugal.